2000
DOI: 10.1161/01.str.31.5.1111
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Pulsatility as an Index of Cerebral Microangiopathy in Diabetes

Abstract: Background and Purpose-This study was designed to evaluate cerebral hemodynamic changes related to diabetes mellitus (DM) with transcranial Doppler ultrasonography (TCD). Methods-We measured the flow velocities and the Gosling pulsatility index (PI) of the middle cerebral artery (MCA), extracranial internal carotid artery (ICA), and basilar artery (BA) in 56 stroke-free, normotensive patients with type 2 DM and 70 age-and gender-matched healthy volunteers. Patients were divided into 2 groups according to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
110
7
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(132 citation statements)
references
References 45 publications
14
110
7
1
Order By: Relevance
“…All TCD studies were performed by a single operator with a three-dimensional mapping instrument (Trans-scan, EME) using examination techniques similar to those previously described [8]. Doppler signals from the left main stem of the middle cerebral artery (MCA) were obtained with a 2-MHz probe attached to a stereotactic headpiece through a transtemporal window at a depth of 62-66 mm, and follow-up TCD in each patient was performed at the same depth to initial examination.…”
Section: Methodsmentioning
confidence: 99%
“…All TCD studies were performed by a single operator with a three-dimensional mapping instrument (Trans-scan, EME) using examination techniques similar to those previously described [8]. Doppler signals from the left main stem of the middle cerebral artery (MCA) were obtained with a 2-MHz probe attached to a stereotactic headpiece through a transtemporal window at a depth of 62-66 mm, and follow-up TCD in each patient was performed at the same depth to initial examination.…”
Section: Methodsmentioning
confidence: 99%
“…Our findings suggest that the vasculature of 30 to 40-yearold polysubstance abusers might be compromised, thus putting them at risk for cerebrovascular accidents (Strandgaard, 1993;Jamrozik et al, 2000), small vessel diseases (Lee et al, 2000;Kidwell et al, 2001), and/or cognitive impairments (Anstey and Smith, 1999;Rabbitt and Lowe, 2000). Our study reveals that treatment with methadone can reduce these abnormalities, although this therapeutic approach did not normalize these measures.…”
Section: Discussionmentioning
confidence: 59%
“…Patients with multi-infarct dementia have reported mean MCA PI values of 1.27+0.15 (Biedert et al, 1995) and of 1.20 (standard deviation not given) (Sattel et al, 1996). Chronic hypertensives (Cho et al, 1997) and diabetic patients (Lee et al, 2000) have been reported to have PI increases, which correspond to means of 0.89 (standard deviation not given) and 0.87+0.22, respectively. Middle cerebral artery PI values were found to be correlated with MRI measures of small vessel diseases characterized by periventricular hyperintensity (PI cutoff point for detection: 1.17), deep white matter hyperintensity (PI cutoff point for detection: 0.96), and lacunar disease (PI cutoff point for detection: 0.96) (Kidwell et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Failure to cushion systolic pulsation due to arterial wall stiffening, results in larger amplitude of intracranial blood beating and microvasculature damage [43;44], and consequent endothelial cell shedding, myocyte damage, BBB failure and vessel rupture [45]. In general, accumulating diffuse microangiopathic disease promotes increased vascular resistance [46][47][48] escalating hypertension and impaired venous outflow [43;49].…”
Section: Discussionmentioning
confidence: 99%